Trichocera (Metatrichocera) mackenziei Dahl 1967 - Petrašiūnas, Andrius; Podėnas, Sigitas (Zenodo, 2011)
Trichocera ( Metatrichocera ) mackenziei (Dahl, 1967) Metatrichocera mackenzie Dahl, 1967. Dahl, 1967a: 60. Trichocera ( Metatrichocera ) mackenziei (Dahl, 1967). Dahl & Alexander, 1976: 14. Illustrated by Dahl, 1967a: figs. 11–15, 57–60; Dahl, 1967b: figs. 12–14; Dahl & Krzemińska, 1997: figs. 34–35; Pratt, 1992: fig. 12; Pratt, 2003: fig. 12. Material examined. MONGOLIA: 1 male, Hovsgol Aimag, Khankh Soum, Noyon river bank, 8–15 August, 2005, Malaise trap, coll. O. Yadamsuren and S. Enkhtaivan, habitat: narrow valley with boggy forb-sedge meadow ( Carex sp., Leymus chinensis , Potentillia sp.), vegetation coverage 70 percent, malaise trap at river edge; 1 female, Hovsgol Aimag, Ulaan Uul Soum, bogs and streams 800 m from Bagtag Gol (river), N50.81208 E99.33510, elevation 1590 m, 30.VI.2006, Selenge River Basin Insect Survey Project # 06062904. The species was known from Northern Canada (Dahl, 1967), Northern Sweden and Finland (Dahl & Alexan- der, 1976) and Russian Kola Peninsula (Lantsov & Chernov, 1987). Lantsov and Chernov (1987) suggested that T. mackenziei could have a boreal distribution and our finding of this species in northern Mongolia agrees with their view. Subgenus Saltrichocera Krzemi ń ska, 2002 Saltrichocera was established for the inclusion of Trichocera species with simple gonostylus and gonocoxite, separated and highly arched bridge, large aedeagal complex with strong and long basal apodemes and rounded to elongate lateral apodemes (Krzemińska, 2002a). Published as part of Petrašiūnas, Andrius & Podėnas, Sigitas, 2011, Notes on winter flies Trichoceridae (Diptera) of Mongolia with description of new species, pp. 61-68 in Zootaxa 3031 on pages 62-63, DOI: 10.5281/zenodo.278712